Essential Oils as Phytogenic Feed Additive: Potential Benefits on Environment, Livestock Health and Production - Dey, Avijit; Misra, S. S.; Dahiya, S. S.; Balhara, A. K.; Kumar, Krishan; Das, A. K.; Singh, R. K.; Attri, Kiran; Imaz, Jose A (International Journal of Economic Plants, 2017)
Essential oils (EOs) are volatile secondary plant metabolites, which provide characteristic aroma and flavour, specific to many plants. They are mainly derived from herbs and spices, and used traditionally by humans for many centuries for their antimicrobial and preservative properties. The term ‘’essential oil’’ is misleading as neither they are ‘’essential’’ for nutrition and metabolism nor ‘’oils’’ as glycerol based lipids. They are aromatic compounds with oily appearance. The phrase “essential” derives from “essence,” which means smell or taste, and relates to the property of these substances of providing specific flavours and odours to many plants. EOs and their components reduce entric methane and ammonia emission by modulating rumen microbial community structure and could be used as phytogenic feed additive. However, their effects need to be studied by long term in vivo experimentation, as adaptation of rumen microbes could lead to ineffectiveness. Optimum dose of bioactive essential oil components and their appropriate combinations needs to be standardized in relation to dietary composition of animals to achieve consistent benefit of their feeding for livestock health and performance before their application in large scale livestock production systems.